Global Macroeconomic Drivers of Gold Prices: The Impact of Inflation, USD Exchange Rate, and Crude Oil Prices - Herman Herman; Antony Wijaya; Afriza Amir; Nur Ahmadi Bi Rahmani (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to examine the influence of the inflation rate, the US dollar exchange rate, and global oil prices on world gold prices. Using a quantitative approach with secondary time-series data, the analysis was carried out through multiple linear regression to identify both partial and simultaneous effects of the selected macroeconomic variables. The findings indicate that the inflation rate does not have a significant impact on gold prices. In contrast, the US dollar exchange rate shows a positive and significant relationship with gold prices, suggesting that fluctuations in the value of the dollar play an important role in shaping global gold market movements. Meanwhile, global oil prices are found to have no significant partial effect on gold prices. Furthermore, when examined simultaneously, the three macroeconomic variables do not exhibit a collective influence on world gold prices. These results highlight the dominant role of currency dynamics compared to inflationary conditions and oil price fluctuations in determining gold price behavior during the observed period.